2015
DOI: 10.3390/ma8125469
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Sodium Titanate Based Materials for Piezoelectric Actuators

Abstract: The ban of lead in many electronic products and the expectation that, sooner or later, this ban will include the currently exempt piezoelectric ceramics based on Lead-Zirconate-Titanate has motivated many research groups to look for lead-free substitutes. After a short overview on different classes of lead-free piezoelectric ceramics with large strain, this review will focus on Bismuth-Sodium-Titanate and its solid solutions. These compounds exhibit extraordinarily high strain, due to a field induced phase tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 156 publications
(278 reference statements)
2
56
0
Order By: Relevance
“…3 The origin of the large field-induced strain was attributed to the coexistence of non-ergodic polar nanoregions(PNRs) with R3c space group and ergodic PNRs with P4bm space group. [4][5][6] Zhang et al observed a giant electrostrictive strain of 0.45% and an strain coefficient of (0.021-0.027) m 4 /C 2 in the 0.94NBT-0.06BaTiO 3 -0.02K 0.5 Na 0.5 NbO 3 . 7 In a word, constructing relaxor ferroelectrics with coexistence of nonergodic and ergodic PNRs is the key to obtain electrostrictive strained materials with hysteresis-free and large strain coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…3 The origin of the large field-induced strain was attributed to the coexistence of non-ergodic polar nanoregions(PNRs) with R3c space group and ergodic PNRs with P4bm space group. [4][5][6] Zhang et al observed a giant electrostrictive strain of 0.45% and an strain coefficient of (0.021-0.027) m 4 /C 2 in the 0.94NBT-0.06BaTiO 3 -0.02K 0.5 Na 0.5 NbO 3 . 7 In a word, constructing relaxor ferroelectrics with coexistence of nonergodic and ergodic PNRs is the key to obtain electrostrictive strained materials with hysteresis-free and large strain coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution of A and B sites is suitable to solve the problem of high coercive electric field. [4][5][6] To overcome the second drawback, one must be decreasing the value of depolarization temperature from 200 C to nearly room temperature in order to enhance the piezoelectric performance. In this research, the substitution of A-site in BNT with Ba þ2 had been done, it had an ionic radius greater than (Bi,Na).…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of the phase transitions in the BNT-BT system below TC is still a matter of debate. A detailed review of the properties of BNT-based materials with regard to actuator applications has recently been reported [9]. …”
Section: Introductionmentioning
confidence: 99%